النظام التعويضي عن الأضرار الناجمة عن المخاطر الكبرى ( الحريق أنموذجا ) - شهيناز مساعدية (My University, 2026)
Abstract : Disaster risks constitute a serious threat that places a heavy burden on societies and States. Once such risks materialize, they turn into devastating disasters that cause substantial damage and significant losses. These disasters may be of natural origin, attributable to divine acts, or of human origin, resulting from human conduct. The compensation regime governing the damages arising therefrom varies according to their classification.With regard to natural disaster risks, the State’s liability to compensate affected persons is established on the basis of the risk theory, as the State is considered the principal and ultimate debtor for those who have no other legal means to seek indemnification. Reparation for such damages is ensured through specific mechanisms, most notably the Agricultural Disaster Guarantee Fund and the Compensation Fund for Damages Resulting from Natural Disaster Risks.As for technological disaster risks, liability is founded on the precautionary principle, and the judicial award of compensation constitutes one of the most significant consequences of establishing civil liability for technological disaster risks. Such compensation may be provisional or final, depending on the nature and extent of the damage. As regards the risk of fire, liability is established on the basis of fault that must be proven on the part of the holder of the immovable or movable property in which the fire originated and spread to the property of others, thereby causing damage. Compensation is considered the legal consequence of the establishment of such liability and may take the form of restitution in kind, by restoring the situation to its previous state, or monetary compensation, assessed on the basis of the loss actually suffered by the injured party as well as the loss of profit. The insurance contract constitutes an effective legal mechanism for the reparation of damages resulting from the risk of fire, whereby the insured is obliged to pay insurance premiums, while the insurance company, in return, undertakes to pay compensation equivalent to the actual loss in the event of the occurrence of the insured fire risk. Such compensation is determined in accordance with a set of carefully designed and accurately applied actuarial and legal rules. ................................ الملخص: تشكل أخطار الكوارث تهديدا يثقل كاهل المجتمعات والدول إذا تحقق وقوعها تصبح كارثة مدمرة تخلف ورائها أضرارا وخسائر فادحة منها ذات المصدر الطبيعي ترجع للقدرة الإلهية ومنها ذات المصدر البشري تكون بفعل الإنسان، ويختلف النظام التعويضي عن الأضرار الناجمة عنها تبعا لاختلاف تصنيفاتها فبالنسبة لأخطار الكوارث الطبيعية تقوم فيها مسؤولية الدولة بتعويض المتضررين على أساس نظرية المخاطر كونها المدين الأعظم والنهائي لمن لا يجد سبيل غيرها لتضمينه وتعويضه ويتم جبر الأضرار من خلال آليات خاصة أبرزها صندوق الضمان على الكوارث الفلاحية، وصندوق تعويض الأضرار الناجمة عن أخطار الكوارث الطبيعية، وبالنسبة لأخطار الكوارث التكنولوجية تقوم المسؤولية على أساس مبدأ الحيطة ويعتبر الحكم بالتعويض من أبرز آثار قيام المسؤولية المدنية عن أخطار الكوارث التكنولوجية الذي قد يكون احتياطي أو نهائي. أما خطر الحريق فتقوم فيه المسؤولية على أساس الخطأ الواجب الإثبات في جانب حائز العقار أو المنقول الذي شب فيه الحريق وتسرب إلى ممتلكات الغير فألحق بها أضرار ويعتبر التعويض جزاء قيام هذه المسؤولية فقد يكون عيني بإعادة الحال إلى ما كان عليه كما قد يكون نقدي ويتم تقديره انطلاقا مما لحق المضرور من خسارة وما فاته من كسب، ويعتبر عقد التأمين آلية قانونية فعالة لجبر الأضرار الناجمة عن خطر الحريق حيث يلتزم المؤمن له بدفع أقساط تأمينية وفي المقابل تلزم شركة التأمين بدفع مبلغ تعويض يساوي الخسارة الفعلية في حالة تحقق خطر الحريق وذلك من خلال جملة من القواعد القانونية الإحصائية المدروسة بعناية ودقة. وخلصت الدراسة بإقرار جملة من التوصيات يجب أخذها بعين الاعتبار لضمان تعويض عادل. ............................ Résumé : Les risques de catastrophe constituent une menace majeure qui pèse lourdement sur les sociétés et les États. Lorsqu'ils se matérialisent, ils se transforment en catastrophes dévastatrices entraînant des dommages considérables et des pertes importantes. Ces catastrophes peuvent être d'origine naturelle, résultant de phénomènes naturels, ou d'origine humaine, découlant des activités ou des comportements de l'homme. Le régime juridique de l'indemnisation des dommages qui en résultent varie selon leur nature. S'agissant des risques de catastrophes naturelles, la responsabilité de l'État en matière d'indemnisation des victimes est fondée sur la théorie du risque. L'État est considéré comme le débiteur principal et de dernier ressort envers les personnes qui ne disposent d'aucun autre moyen juridique leur permettant d'obtenir réparation. L'indemnisation de ces dommages est assurée au moyen de mécanismes spécifiques, notamment le Fonds de garantie contre les calamités agricoles et le Fonds d'indemnisation des dommages résultant des risques de catastrophes naturelles. En ce qui concerne les risques de catastrophes technologiques, la responsabilité repose sur le principe de précaution. L'octroi judiciaire d'une indemnisation constitue l'une des principales conséquences de l'établissement de la responsabilité civile en matière de risques technologiques. Cette indemnisation peut être provisoire ou définitive, selon la nature et l'étendue du dommage subi. Quant au risque d'incendie, la responsabilité est fondée sur la faute, laquelle doit être prouvée à l'encontre du détenteur du bien immobilier ou mobilier dans lequel l'incendie s'est déclaré avant de se propager aux biens d'autrui et d'y causer des dommages. L'indemnisation constitue la conséquence juridique de l'établissement de cette responsabilité. Elle peut prendre la forme d'une réparation en nature, consistant à rétablir la situation antérieure, ou d'une réparation par équivalent pécuniaire, évaluée en fonction de la perte effectivement subie par la victime ainsi que du gain manqué. Le contrat d'assurance constitue un mécanisme juridique efficace de réparation des dommages résultant du risque d'incendie. L'assuré est tenu de verser les primes d'assurance, tandis que l'assureur s'engage, en contrepartie, à indemniser l'assuré à hauteur du préjudice réellement subi lorsque le risque d'incendie couvert par le contrat se réalise. Cette indemnisation est déterminée conformément à un ensemble de règles actuarielles et juridiques rigoureusement élaborées et appliquées. L'étude s'achève par la formulation d'un ensemble de recommandations qu'il conviendrait de prendre en considération afin de garantir une indemnisation juste et équitable.
Keywords: Keywords : Disaster Risks; Fire Risk; Compensation; Insurance; Damages.; الكلمات المفتاحية: أخطار الكوارث؛ الحريق، التعويض، التأمين، الأضرار.; Mots-clés : Risques de catastrophe; Risque d'incendie; Indemnisation; Assurance; Dommages.